Spatial and temporal changes in Halal food sales and consumption. A case study of the city of Dearborn, Michigan. Issue 2 (4th May 2021) - Roodbar, Sam; Veeck, Gregory
ABSTRACT: With a population of 3.5 million and growing in the US, Middle Eastern / North African (MENA) Americans are an integral part of the United States and the world. One of the main agents of cultural maintenance and support for the MENA American community are their ethnic food traditions, specifically Halal food. Since the introduction of Halal food in the US, sales and consumption of Halal products has increased immensely. This research seeks to answer four related questions focused on the entrance of larger, retail food corporations into this market segment traditionally occupied by smaller scale, ethnic food stores. An online survey of Halal food purchasers forms the core of this mixed method research project which also includes informal interviews with store owners, and survey of Dearborn's business directories. MENA Americans are young, highly educated, and dedicated to their culture and heritage. Interestingly, for this population "religious reasons" remain to be the most important influencing factor when purchasing Halal food. Analyzed in light of the political climate of the time, the results of this study illustrate that the rise of Halal food can be better understood as a form of cultural resistance against the prejudice that the MENA Americans face.